From tribute to taxpaying: the changes in the understanding of private property in Denmark circa 1000–1250 - Vogt, Helle (Danish Journal of Archaeology, 2017)
The focus of the paper is about how the concept of property and the possession of land changed in Denmark from c. 1000 to 1250. Until the mid of the twelfth century, we are mostly depending of the archaeological material and the few narrative sources, and they give an impression of a system where various persons could have rights and claims to the same landed property – the farmer who cultivated it, the local lord who had a right to tribute, and his lord – the king. This system was challenged when the Church was established in the eleventh and twelfth century and started to get large donations. The Church claimed full property right the donated land, something that lead to conflicts, and one response was the introduction if written laws with firm rules about transfer of landed property and ownership. The introduction of firm rules did not mean that kinsmen stopped questioning donations or sales of land to ecclesiastical institutions in the thirteenth century, but rather that the conflicts were legalised.